La nouvelle histoire du droit - Belley, Jean-Guy (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1986)
The collective book edited by G. Rubin and D. Sugarman, Law, Economy and Society, 1750-1914 : Essays in the History of English Law (1984) is well illustrative of the main trends of the new history of law that is now flourishing particularly in England and the United States. The twelve studies conducted by the contributors reveal the diversity of theoretical issues, subjects of inquiry, methodological strategies and sources of data that characterize the new history of law. In contrast with the more traditional and formal history of legal institutions, the entire book also expresses the critical stance the discipline is seeking to adopt, relying on sociology and other social sciences in order to apprehend law from an external rather than merely doctrinal point of view.